Positron emission tomography/computed tomography scan of Vogt–Koyanagi–Harada syndrome with associated autoimmune thyroid disease: A case report and literature review. Issue 9 (March 2018) - Huang, Ke-Hao; Tai, Ming-Cheng; Lee, Lung-Chi; Weng, Tzu-Heng; Chen, Yi-Hao; Lin, Li-Fan; Chen, Jiann-Torng; Lu, Da-Wen; Chen, Ching-Long
Abstract: Rationale: Vogt–Koyanagi–Harada (VKH) syndrome is a rare disease and could be associated with autoimmune thyroid disease (AITD). This report was aimed to investigate the utility of 18 F-fludeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) for the diagnosis of VKH syndrome with AITD and to perform a literature review on the association between the 2 diseases. Patient concerns: A 55-year-old woman without the history of ocular trauma suffered from chronic headache. She was presented with painful blurred vision of both eyes with headache for 2 weeks. Ophthalmic evaluations revealed panuveitis, exudative retinal detachment, and papilloedema in both eyes. The clinical symptoms and presentations are compatible with the diagnosis of VKH syndrome. Other examinations for intraocular infection, malignancy, and lupus choroidopathy were of negative results. The result of contrast-enhanced computed tomography (CT) of the brain was normal. Due to the history of cancer in the patient's families, a 18 F-FDG PET/CT whole-body scan was performed. The result indicated a focal of 2-fluoro-2-deoxy-D-glucose (FDG) uptake at the right upper lobe of the thyroid. Therefore, the patient's thyroid function was examined and the result indicated euthyroidism with detectable thyroid peroxidase/thyroglobulin antibodies. Diagnoses: VKH syndrome with associated AITD. Interventions: Treatment with intravenous pulse systemic methylprednisolone (1000 mg daily) was prescribed for 3 days and then shifted gradually to tapered oral steroid medication. Outcomes: Symptoms of papillitis and serous retinal detachment of VKH syndrome was relieved after steroid treatment Lessons: 18 F-fludeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) can be used for the effective diagnosis of VKH syndrome with AITD.